7 - The Role of the Family, Kinship and Rural / Urban Migration in the Processing of Solid Waste in Cairo - Ef-Hakim, Shérif Mahmoud (Africa Development, 1977)
This paper (I) is directed mainly at issues seldom discussed sociologists but which are current in the recent concern for environment and the formation of social policy strategies. Quite unlike the cities of Europe and North America, Cairo no publicly organised solid waste disposal system. Instead, little cost to the public, the waste from the dwellings of the million people of Cairo is almost entirely digested within the city This paper describes how such economic and ecolqgical efficiency is achieved trough kinship solidarity, migration and cross-relations. In cooperation with a community of migrants originally from the Western Desert ; squatter communities systematically the urban domestic waste into marketable components and raise A steady influx of new migrants absorbs the increasing volume waste due to the expanding city and replaces retiring vertically old migrants. Development strategies and the issue of the costs of the system is discussed in the final section